Knowledge and Data Sharing - Annual Technical Report 2024 - Tobon, Hector; Gamboa, Cristian; Morales, Tatiana; Tanaka, Kenji (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This report presents an overview of the strategic and technical contributions made by the Knowledge and Data Sharing team in 2024 to enhance information and results management within the AICCRA project. Central to these efforts was the continued development and optimization of the MARLO tool, which now plays a critical role in fostering a culture of monitoring, evaluation (M&E), and results-oriented project management. These updates have significantly improved the integrity, quality, and impact of research outputs. The report highlights how improvements to MARLO and the implementation of the Data Management Plan—aligned with new funding streams and the revised results framework—have strengthened the project’s ability to deliver high-quality, verifiable results. By promoting open access principles and evidence-based approaches, the team has ensured that project outcomes are not only publicly available but also actionable, ultimately supporting more informed decision-making in the agricultural sector across Africa. In summary, the report describes the main system improvements, progress in digital integration, and the skills development that took place within the Knowledge and Data Sharing team itself. These actions helped the team better support project staff with planning and reporting, allowing for more efficient and coordinated work across the AICCRA initiative.